ANALYSIS OF THE CORRELATION BETWEEN INVESTMENTS, THE REAL COST WITH LABOR AND TOTAL EMPLOYABILITY IN THE EU, IN THE ECONOMIC CONTEXT MARKED BY THE COVID-19 PADEMIC - SILVESTRU, Cătălin Ionuț; IFRIM, Ana-Maria; SILVESTRU, Ramona Camelia; ONCIOIU, Ionica; Bitan, Gabriela Elena; OLARU, Stelian-Mircea (Ecoforum Journal, 2021)
The objective of the study conducted by the authors is the analysis of the impact of two indicators - the total value of investments and the real cost of labor - on the indicator total employability, in the current economic context, marked by the COVID-19 pandemic. To achieve this goal, the linear regression model was used in the analysis of the correlation between total employment, real unit labor costs and total investment volume. As a result of determining the correlation coefficients, it turned out that the number of employees depends largely on the total value of investments, which has a major impact on the labor market. On the other hand, it turned out that, in the current economic context, the need for jobs is much higher and employability no longer depends on real unit labor costs. These results are consistent with existing theoretical studies. We consider that the estimates made on the impact of the total value of investments and the real cost of labor on employability are useful in testing and implementing theories of investment and consumption in conditions of uncertainty.